Reaction of a polydentate cysteine-based ligand and its nickel(ii) complex with electrophilic and nucleophilic methyl-transfer reagents – from S-methylation to acetyl coenzyme A synthase reactivity. Issue 42 (21st September 2015) - Warner, D. S.; Limberg, C.; Oldenburg, F. J.; Braun, B.
Abstract : A cysteine-based nickel(ii ) complex reacts with methylating reagents followed by CO treatment via acetylation of the thiolate function corresponding to the ACS reactivity. Abstract : Thel -cysteine derived N2 S2 ligand precursor H2 L and its nickel(ii ) complex L2 Ni2 were investigated with respect to their behaviour in contact with electrophilic and nucleophilic methylation reagents (H2 L = ( N, N ′-dimethyl-(2 R, 5 R )-bis-(sulfanylmethyl)-piperazine). Treatment of deprotonated L 2− with MeI led to the selective methylation of the thiolate groups thus generating a novel potential ligand, Me2 L, which is neutral and contains two thioether donors. The coordinating properties of Me2 L were demonstrated by the synthesis of a first nickel(ii ) complex: reaction with NiBr2 led to a mononuclear complex2 where all donor atoms coordinate to the nickel ion, which completes its octahedral coordination sphere by the two bromide ligands. If, however, the complex [LNi]2 (1 ) is treated with MeI only one thiolate function per ligand moiety is methylated, while the other one remains a thiolate. This leads to [MeLNi] + complex metal fragments, which trimerize including a μ3 -bridging iodide ion to give the compound3 that was tested with regards to ACS reactivity. While it behaved inert towards CO, attempts to replace the bridging iodide ligand by methyl units in reactions with nucleophilic methylation reagents led to a product, which could not be identified but reacted with CO. Work-up showed that this protocol had converted the thiolate function of MeL − into a thioester function, which corresponds to an ACS-like reactivity.